The role of nanoparticle-gemini surfactant to improve the flowability of the Malaysian crude oil - VijayaKumar, Shamala Devi; Junaidi, Zakaria; Norida, Ridzuan (Springer, Singapore, 2021)
Wax deposition on the inner walls of transportation pipelines and production equipment of Malaysian crude oil had been identified as one of the main encounters in the crude oil industry which leads to serious problem in crude oil flow assurance. In this research, the performance of a Gemini surfactant, nanoparticle and their blends are assessed to study their impacts on the viscosity of crude oil usingrheometer.Silicondioxide(SiO2)(200–600ppm)alongwithGeminisurfactant (ethoxylated-2,5,8,11-tetramethyl-6-dodecyn-5,8-dio) (200–1000 ppm) at different temperature (10–30 °C) were studied to discover the effect on viscosity. From the results, the most efficient viscosity reducing concentration of Gemini surfactant, nanofluid and nanoparticle-Gemini surfactant was found at the concentration of 400 ppm, 300 ppm and 200 ppm, respectively. At 30 °C and 80 rpm, the viscosity of the crude oil is reduced from 3.75 to 3.5 cP compared to the blank crude oil. Addition of SiO2 nanoparticle to Gemini surfactant, resulted in reduction of viscosity of the crude oil from 3.75 to 1.5 cP. At temperature 10 °C, Gemini surfactant reduced the viscosity of crude oil from 51.95 to 4.5 cP, while the addition of SiO2 nanoparticle only reduced the viscosity from 51.95 to 3.75 cP. As a conclusion, the addition of nanoparticle-Gemini blend shows the significant result at low temperature where it shows the best reduction of crude oil viscosity.